Ureditev nekaterih institutov individualnih delovnih razmerij danes in v prihodnje - Tičar, Luka (Delavci in delodajalci, 2018)
First of all, the author wishes to emphasize the progress that was made on the normative level of the regulation of individual labour relations in the Republic of Slovenia. He particularly emphasizes and extracts some of the most important legal solutions, which suggest that Slovenia has relatively good and up-to-date legal solutions, especially when put in the international legal context. Nevertheless, the author wishes to draw attention to a number of institutes and legal solutions which could, with minor changes, place the existing regulation to a higher level. Within this context, the author discusses the systematisation act as the basis for the conclusion of an employment contract, the problematics of two non-standard forms of employment and some elements of the regulation of working time and payment for work in the broadest sense.
Keywords: akt o sistemizaciji; break during the working hours; delovno pravo; fixed-term employment contract; full-time work; justified reason for regular termination of employment contract; odmor med delovnim časom; omejevanje sklepanja pogodbe o zaposlitvi za določen čas; polni delovni čas; povračilo stroškov v zvezi z delom; reimbursement of labour costs; Systematisation Act; utemeljen razlog za redno odpoved pogodbe o zaposlitvi